2013
DOI: 10.5751/es-05769-180329
|View full text |Cite
|
Sign up to set email alerts
|

Using Short-Term Monitoring Data to Achieve Goals in a Large-Scale Restoration

Abstract: ABSTRACT. To evaluate the outcome of restoration projects, an overall goal, reformulated to specific subgoals or targets, must be explicit and translated into scientifically measurable ecological attributes. Monitoring ecological attributes is necessary to assess restoration progress. Data from long-term monitoring are rarely available when restoration interventions are planned and implemented. In this study, we show how short-term monitoring data are incorporated into the planning of the large-scale restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 42 publications
1
59
1
1
Order By: Relevance
“…While fertilizer was not used in this project due to proximity to the aquatic environment, the use of fertilizers is often deemed necessary in arctic revegetation projects to promote plant growth, especially for non-native species, as the uppermost soil layer which generally contains nutrients and soil bacteria that help cycle nutrients has generally been disturbed or removed by human activities [10] [17]. However, in some arctic environments, the use of fertilizers may be detrimental to some plants that are adapted to growing in nutrient-poor environments, or if non-native species become established due to a higher nutrient content, they may prevent re-colonization by native species through formation of a dense vegetation mat that is not easily penetrated [6] [13] [31]. For example, a study by Klokk and Rønning [10], determined that the effectiveness of fertilizer treatments on seven native species in Norway appeared to be species-specific.…”
Section: Initial Plant Survey Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While fertilizer was not used in this project due to proximity to the aquatic environment, the use of fertilizers is often deemed necessary in arctic revegetation projects to promote plant growth, especially for non-native species, as the uppermost soil layer which generally contains nutrients and soil bacteria that help cycle nutrients has generally been disturbed or removed by human activities [10] [17]. However, in some arctic environments, the use of fertilizers may be detrimental to some plants that are adapted to growing in nutrient-poor environments, or if non-native species become established due to a higher nutrient content, they may prevent re-colonization by native species through formation of a dense vegetation mat that is not easily penetrated [6] [13] [31]. For example, a study by Klokk and Rønning [10], determined that the effectiveness of fertilizer treatments on seven native species in Norway appeared to be species-specific.…”
Section: Initial Plant Survey Resultsmentioning
confidence: 99%
“…[10] [11]. Slow-growing woody perennials such as Dryas integrifolia, Salix arctica, and Saxifraga oppositifolia are often undetectable or do not provide significant plant cover until much later in the natural succession process, if at all [11]- [13]. As species turnover is low in arctic and alpine ecosystems, early colonizing species may become part of the late successional stage.…”
Section: Introductionmentioning
confidence: 99%
“…They found that interactions were generally satisfactory, but also that well-functioning interactions were necessary for positive results. Hagen and Evju (2013) also stressed the importance of good and continued interactions between different actors of ecological restoration, both to improve commitment and endurance of the actors and to accommodate potential future changes that might result from adaptive management.…”
Section: Legislation Policy and Implementation Of Restorationmentioning
confidence: 99%
“…As an example of method development, Hagen and Evju (2013) present the results of a pilot project in the Norwegian mountains and its implications for larger-scale restoration. In their project, the revegetation of a former military area by three different techniques was evaluated, showing fairly convergent results with time.…”
Section: Setting Objectives and Evaluating Restoration Outcomesmentioning
confidence: 99%
See 1 more Smart Citation